Students’ Perception of Ideal English Teachers in SMPN 19 Kendari - Masniah Masniah; Kamaluddin Kamaluddin; Tambunan Tambunan (Halu Oleo University, 2020)
This study aimed to describe the ideal type of English teachers in terms of their competencies from the students’ point of view. Respondents of this study were 18 students of 9th grade students of SMPN 19 Kendari. Data collection techniques included open-ended and close-ended questionnaires and interviews. Data analysis was conducted using content analysis. Content analysis revealed a number of competencies associated with an ideal English teacher. As far as the students are concerned, an ideal English teacher should have pedagogical competencies, personal competencies, professional competencies, and social competencies. Each of these competencies along with its characteristics will be presented and discussed in this paper.Keywords: Ideal Teacher, Good Teacher, Teacher competence, Perception.